2020
DOI: 10.21203/rs.2.16335/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect Of Sleeping Position On Heart Rate Variability In Newborns

Abstract: Background : Lower heart rate variability (HRV) in a newborn might represent a risk factor for

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Preterm infants who can have decreased gastric motility needing the right lateral position and also suffer from symptoms of gastric reflux requiring the left lateral position (Elser, 2012). Sleeping in a supine position could have some advantages in prevention of sudden infants death syndrome than in prone position but not used for minimizing regurgitation (Fister, Nolimal, Lenasi and Klemenc, 2020). According to Park, Pados and Thoyre (2018) found that right side lying position is beneficial for supporting physiologic stability during feeding.…”
Section: Present Regurgitation Episodesmentioning
confidence: 99%
“…Preterm infants who can have decreased gastric motility needing the right lateral position and also suffer from symptoms of gastric reflux requiring the left lateral position (Elser, 2012). Sleeping in a supine position could have some advantages in prevention of sudden infants death syndrome than in prone position but not used for minimizing regurgitation (Fister, Nolimal, Lenasi and Klemenc, 2020). According to Park, Pados and Thoyre (2018) found that right side lying position is beneficial for supporting physiologic stability during feeding.…”
Section: Present Regurgitation Episodesmentioning
confidence: 99%